Estágios curriculares e práticas de ensino supervisionadas: sentidos e significados apreendidos por alunas de um curso de pedagogia - Silvestre, Magali Aparecida (2008)
The present study aims at highlighting the importance of the spaces for supervision of curricular periods of training as basic for the initial formation. For such, the apprehension of meanings and senses on supervised teaching practice by students from the Pedagogy course was the central object of analysis. It is a qualitative research that had as methodological and theoretical reference a social and historic approach. Initially, the context in which the research s problematic was found is introduced aiming at delineating this study s main focus. With the objective of justifying the scientific relevance of this research and having as its basis the State of Art in Teachers Education, the sequence of the text mainly identifies how scarce the production of knowledge related to the subject of supervised training is, especially those carried through in the courses of Pedagogy. The first chapter goes briefly over how teacher education was conceived along the Brazilian education s history and how teaching practice and supervised practice have been incorporated in the process of initial formation. In the second chapter, the suggested and defended model of initial formation is enclosed aiming at demonstrating the importance of overcoming models based on a technical rationale as well as on a practical one. This overcoming is believed to lead us to the formation of a professional capable of politically and historically contextualize the teaching-learning process, setting their practice and understanding it as a social practice which entices citizens and subjectivities and that must intentionally influence the reality it s in. The third chapter presents the contribution of social-historical psychology represented by authors as Leontiev and Vigotski, among others, who use this approach to explain psychic phenomena apprehending the singularity of the human being. The intention was to control the inquiry s focus on the object of this study: the supervised practice in the courses of teacher education by means of curricular periods of training, presenting theoretical references which allowed the combination of meanings and senses apprehended by students that attend the course of Pedagogy and that have been through this experience. After that, the methodological procedures and the information of the carried through interviews are presented. This resulting information allowed us to arrive at the nuclei of meanings that had been discussed having as its basis the theoretical support from the first chapters. Finally, this study is closed with the presentation of a summary of the produced knowledge constituted as the initial hypotheses meanings were discovered and while the direction all this study denoted to the formation and professional identity of the own researcher was understood. As a consequence of the thesis some aspects to be considered on the construction of pedagogical projects for the courses of teacher initial education are mentioned, especially those related to the concept and organization form of the supervised curricular periods of training